Policing, Detention, Deportation, and Resistance: Situating Immigrant Justice and Carcerality in the 21st Century - Lawston, Jodie Michelle (Social justice, 2009)
This article discusses problems related to the detention of immigrants in the United States. The article mentions that the Corrections Corporation of America has announced plans to construct the largest immigration detention center in the U.S. in San Diego, California. It has been reported that many detained immigrants are subjected to abuse. Abuses range from inadequate health care to the rape of female prisoners. The article presents a history of the treatment of immigrant detainees from the passage of the Immigration Reform and Control Act in 1986 and discusses possible ways to enforce immigration laws in the future.